Current status and economic value of insect-pollinated dependent crops in Latin America - Basualdo, Marina; Cavigliasso, Pablo; Avila Jr., Rubem Samuel de; Aldea-Sánchez, Patricia; Correa-Benítez, Adriana; Martínez Harms, Jaime; Ramos, Ana Karen; Rojas-Bravo, Valeska; Salvarrey, Sheena (Elsevier, 2022)
Latin America (LA) plays an important role in the global food supply and dedicates a significant part of its surface to croplands. Current losses of wild and managed pollinators are a threat to agricultural production because the productivity of many crops depends on entomophilous pollination; thus, consequences could be significant for the development of regional economies. We assess the current importance of pollination service for the main crops of Argentina, Brazil, Chile, Mexico, and Uruguay, which represent approximately 74% of the total surface of LA. Our study focused on three aspects, i) analyses of crops with varying degrees of pollinator dependence in terms of the harvested area and its yield, ii) estimation of economic value attributed to pollinators (EEV) and the vulnerability of each crop category, iii) characterization of the pollinator services provided by managed bees. Regional-level analyses showed that 58% of crops have essential and high dependence levels on insect pollination. LA produced 228.1 million tons of food that can be attributed directly to insect pollination, and an additional 33.9 million tons corresponds to crops that are not directly used for human food. The total production economic value of all crops dependent on pollination was US$ 77.82 billion, of which the economic value attributable to insect pollination was US$ 22.95 billion. Industrial crops and fruits were the leading crop category in the value of entomophilous pollination, followed by beverages, vegetables, hybrid seeds, citrus, and nuts. Crops occupy an area of 64.8 million hectares, 80% of which is used for soybean production, a clear sign of poor agricultural diversification, with Chile and Mexico being the countries with the highest degree of diversification. We estimated that hybrid seeds, fruits, and beverages whose productivity reached 44 million tons, are the most vulnerable to pollinator decline with 90, 64, and 44% vulnerability ratios. Our valuation demonstrates the vulnerability of agrosystems production, socioeconomic, and ecological terms.